Action Learning and the Implementation of Kaizen: Challenges in the Indian Cultural Context - Kunju Kunju Mathew, Sagi (2013)
The aim of this paper is to investigate some of the learning challenges arising from the introduction of the practice of kaizen at a Japanese automobile transplant in India, with particular reference to cultural constraints. The purpose of this study arises from the investigation of long industrial unrest in this plant, a phenomenon unheard of with the parent company globally. It is intended to provide an insight into parallels between action learning and kaizen, to identify common factors in both, and to assist in a wider understanding of organisational learning. A second intention is to highlight the importance of the cultural values of employees in adopting a foreign practice that requires them to make it part of their daily work discourse.